How covid-19 has exacerbated LGBTQ+ health inequalities. (16th March 2021) - Phillips, Callum
Abstract : Despite inadequate monitoring of health in the LGBTQ+ community, the data we have suggest a disproportionate effect of the covid pandemic and its control measures, writes Callum Phillips